Ejecución presupuestaria del Gobierno Autónomo Descentralizado Municipal del cantón Ventanas, período 2023. - Palacios Soria, Joselyn Thalya (2024)
The present study addressed the challenges encountered in the budget execution of the Municipal Decentralized Autonomous Government of the Ventanas canton during the period 2023, characterized by a significant discrepancy between the budgeted income and those actually used. This situation raises questions about the effectiveness of financial management and transparency in the administration of public funds in the municipal entity. The main objective of the study was to examine in detail the budget items of the Municipal GAD of Ventanas to identify factors that affected budget execution and propose recommendations to improve planning and efficient use of resources. The implementation of effective strategies to increase own income and reduce dependence on external sources is crucial to strengthen the fiscal sustainability of the Municipal GAD. Improving fiscal management and adopting more efficient administration practices are key measures to optimize budget execution and ensure equitable and transparent allocation of public resources. This study highlights the importance of addressing identified deficiencies in local budget management, not only to improve the quality of public services and community projects, but also to strengthen the trust and legitimacy of local government in the eyes of citizens. The implementation of these recommendations not only benefits the Municipal GAD of the Ventanas canton, but also establishes a precedent for continuous improvement in local public administration.